The Role Of Brand Image In Mediating Brand Awareness, Social Media Marketing And Price Perception Towards The Purchase Intention Of Customers Wedding Organizer Renjana Project - Adinda Janatri Arifah; Bambang Irawan; Deasy Wulandari (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to examine the influence of brand awareness, social media marketing, and price perception on purchase intention, with brand image as a mediating variable in the context of the wedding organizer industry. The core research problem addressed is the low conversion of purchase intention despite active social media engagement and growing brand exposure. Unlike previous studies that typically examine these variables in isolation or focus solely on direct effects, this research positions brand image as a central psychological mechanism that explains consumer decision-making. A quantitative approach was employed using Covariance-Based Structural Equation Modeling (CB-SEM) via AMOS, with data collected from 190 respondents through an online questionnaire. CFA results confirmed that all constructs are valid and reliable, and the data met the normality assumption. The findings reveal that brand awareness, social media marketing, and price perception significantly affect brand image; brand image, in turn, has the strongest direct influence on purchase intention and mediates the indirect effects of the three antecedents. This study contributes novel theoretical insights to the service marketing literature by emphasizing the pivotal role of brand image in translating brand communication strategies into consumer purchase behavior.